Pemanfaatan Limbah Air Cucian Beras Sebagai Pupuk Organik Cair (POC) (Fakultas Teknik, Universitas Brawijaya, 2025)
Community service is one of the activities carried out by the academic community to promote the welfare of society and to enlighten the nation. This service aims to increase awareness and sustainable practices in the management of domestic organic waste, particularly rice washing water, resulting in Organic Liquid Fertilizer (OLF). Through socialization and demonstration programs, the community is encouraged to transform waste into valuable resources such as OLF. Initial surveys showed a low level of public knowledge about the benefits of OLF. The survey results indicated that 6% of households had already processed rice washing water, while 96% had not. Following the program, there was a significant increase in the community's understanding of the OLF production process, its nutritional content, and its positive impact on plant growth. Additionally, this program contributed to the reduction of randomly discarded organic waste, thereby positively affecting the surrounding environment. The research findings show that intensive and participatory socialization is the key to successful behavior change towards more sustainable agricultural practices